N-Arylation of Sterically Hindered NH-Nucleophiles: Copper-Mediated Syntheses of Diverse N-Arylindole-2-carboxylates - Lee, Jinyong; Choi, Ji Hye; Shin, Seunghoon; Heo, Jung-Nyoung; Lim, Hwan Jung (Synthesis, 2015)
Indole-carboxylates are N-arylated with 2-bromopyridines using stoichiometric copper(II) oxide/potassium carbonate to give various N-(2-pyridyl)-substituted indole-2-carboxylates and with bromobenzenes using stoichiometric copper(I) iodide/N,N′-dimethylethylenediamine to give various N-(substituted phenyl)-substituted indole-2-carboxylates. These results expand the scope of metal-catalyzed N-arylation using heterocyclic amines with steric bulk and weak nucleophilicity.
Keywords: copper; N-arylation; indoles; copper-mediated synthesis; heterocyclic amines; metal-catalyzed